Efeito de protocolos de cimentação na carga de fratura para uma cerâmica de dissilicato de lítio - Carvalho, Rodrigo Furtado de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
It was proposed to evaluate the load of fracture of a ceramic restoration-based lithium disilicate (IPS e.max CAD) submitted to different protocols cementation. 70 bases were made of a resin material similar to dentin (NEMA grade G10) to provide standardized preparations, machined to simulate a tooth prepared for full crown (ending Bevel with walls of 6 degrees of convergence) and the anatomy of the root. The root portion was covered with polyurethane poliétere included. Seventy ceramic crowns were fabricated by CAD / CAM system. After evaluating the film thickness of cement (cement analogue technique) crowns were cleaned with distilled water in ultra-som (5 min). Subsequently, the crowns were subjected to different protocols cementation: FZ-zinc phosphate cement; IVMR-ionomer resin modified glass; RDCS-hydrofluoric acid 5% (20 s) + silane (1 min) + dual resin cement , RDCST-hydrofluoric acid 5% (20 s) + silane (1 min) + heat treatment furnace 100 °C (2 min) + dual resin cement; RDS-silane (1min) + dual resin cement; RDST silane (1 min) + heat treatment furnace 100 °C (2 min) + dual resin cement; RAACS-hydrofluoric acid 5% (20 s) + silane (1 min) + self-adhesive resin cement. All samples were subjected to thermomechanical cycling (2,000,000 cycles - 100N, 4 Hz, 5 ºC - 55 ºC, dwell time 60 s), with a stainless steel piston (Ø = 4 mm) in the center of the occlusal surface. The fracture toughness test was performed in a universal testing machine (v = 1 mm/min at 37 ° C in distilled water). Data fracture resistance (N) were subjected to ANOVA (one factor) and Tukey's test with α = 0.05. We conducted a finite element analysis to check the distribution of the stresses on the crown. Through scanning electron microscopy were performed on two samples from each group, representative photomicrographs of surface treatment . For fractographic analysis, we used the stereo type of fracture...

Foi proposto avaliar a carga de fratura de restauração cerâmica à base de dissilicato de lítio (IPS e.max CAD) submetida a diferentes protocolos de cimentação. Foram confeccionadas 70 bases de um material resinoso análogo à dentina (NEMA grade G10) simulando de maneira padronizada dentes preparados para coroa total (término em chanfro com paredes de 6 graus de convergência) e a anatomia da raiz. A porção radicular foi coberta com poliéter e incluída em poliuretano. Setenta coroas cerâmicas foram fabricadas pelo sistema CAD/CAM. Depois de avaliar a espessura do filme de cimento (técnica do cimento análogo) as coroas foram limpas em ultra-som com água destilada (5 min). Posteriormente, as coroas foram submetidas a diferentes protocolos de cimentação: FZ-cimento de fosfato de zinco; IVMR-cimento de ionômero de vidro modificado por resina; RDCS-ácido fluorídrico 5 % (20 s) + silano (1 min) + cimento resinoso dual; RDCST-ácido fluorídrico 5% (20 s) + silano (1 min) + tratamento térmico forno 100 °C (2 min) + cimento resinoso dual; RDS-silano (1 min) + cimento resinoso dual; RDST-silano (1 min) + tratamento térmico forno 100 °C (2 min) + cimento resinoso dual; RAACS-ácido fluorídrico 5% (20 s) + silano (1 min) + cimento resinoso auto-adesivo. Todas as amostras foram submetidas à ciclagem termomecânica (2.000.000 ciclos - 100 N, 4 Hz, 5 ºC - 55 ºC, tempo de permanência 60 s), com um pistão de aço inoxidável (Ø=4mm) no centro da superfície oclusal. O teste da carga de fratura foi realizado em uma máquina de ensaios universal (v = 1 mm/min à 37 °C em água destilada). Os dados de carga de fratura (N) foram submetidos aos testes ANOVA (um fator) e Tukey, com α = 0,05. Realizou-se a análise de elementos finitos para verificação da distribuição das tensões na coroa. Por meio do microscópio eletrônico de varredura foram realizadas, em duas amostra de cada...
Keywords: Cerâmicas odontológicas; Materiais dentários; Resistencia de materiais; Dental ceramics